Santiago de Chile, new architecture and public space. Architecture of the end of the crisis. 1999-2004. - Aránguiz P., Javier (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2004)
This article deals with a comparative study of present chilean architecture concentrated in the city of Santiago. It points out the importance of a comprehensive thought process capable of integrating single and unrelated enterprizes to urban systems. This is accomplished by coordinating different scales and functions in order to search for the opportunity to reach a better result in terms of urban morphology and urban functions.